2022
DOI: 10.1038/s41467-022-28293-w
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP signalling and glucose metabolism mediate pH taxis by African trypanosomes

Abstract: The collective movement of African trypanosomes on semi-solid surfaces, known as social motility, is presumed to be due to migration factors and repellents released by the parasites. Here we show that procyclic (insect midgut) forms acidify their environment as a consequence of glucose metabolism, generating pH gradients by diffusion. Early and late procyclic forms exhibit self-organising properties on agarose plates. While early procyclic forms are repelled by acid and migrate outwards, late procyclic forms r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 68 publications
(88 reference statements)
3
58
0
Order By: Relevance
“…6e , is based on orthogonal evidence from pull downs and super-resolution microscopy in PCF as well as AlphaFold structure predictions of CARP3 in complex with PCF-specific AC isoforms. CARP3-ACP3 and −5 interaction was also recently shown by Shaw, et al 52 and a proximity proteomics study in PCF identified CARP3 as putative ACP1 interactor 17 . Phenotypes upon expression of deletion mutants of the ESAG4 cyclase are in full agreement with the high confidence prediction of an interface between the conserved AC catalytic core domain and two N-terminal helices of CARP3.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…6e , is based on orthogonal evidence from pull downs and super-resolution microscopy in PCF as well as AlphaFold structure predictions of CARP3 in complex with PCF-specific AC isoforms. CARP3-ACP3 and −5 interaction was also recently shown by Shaw, et al 52 and a proximity proteomics study in PCF identified CARP3 as putative ACP1 interactor 17 . Phenotypes upon expression of deletion mutants of the ESAG4 cyclase are in full agreement with the high confidence prediction of an interface between the conserved AC catalytic core domain and two N-terminal helices of CARP3.…”
Section: Discussionsupporting
confidence: 65%
“…CARP3 deletion completely blocks trypanosome SoMo (Fig. 1 and 52 ), and interestingly, the absence of CARP3 from the flagellar tip (in flam8 KO and carp3∆3 ) is alone sufficient for this phenotype. SoMo phenotypes produced by mutant CARP3, ACs 7 , 52 and PDEB1 8 , 9 together provide strong evidence that cAMP signaling is controlling SoMo.…”
Section: Discussionmentioning
confidence: 87%
“…Flagellar cAMP signalling appears to play a key role in trypanosome SoMo. Inhibiting the flagellar-bound cAMPspecific phosphodiesterases B1 (PDEB1) in trypanosomes, which hydrolyses cAMP, causes increased intracellular cAMP levels, abolishes pH-taxis (Shaw et al, 2021) and blocks SoMo, without impacting the viability or motility of individual cells (Oberholzer et al, 2015). Importantly, PDEB1 null mutants are trapped in the lumen of the tsetse midgut, demonstrating that flagellar cAMP signalling is essential for crossing the peritrophic matrix and completing the lifecycle in the insect (Shaw et al, 2019).…”
Section: The Trypanosome Flagellum Is a Sensory Organellementioning
confidence: 99%
“…Importantly, PDEB1 null mutants are trapped in the lumen of the tsetse midgut, demonstrating that flagellar cAMP signalling is essential for crossing the peritrophic matrix and completing the lifecycle in the insect (Shaw et al, 2019). Two other flagellar-bound sensory proteins, adenylate cyclase 5 (ACP5), and cAMP response protein 3 (CARP3) also appear to be involved in the response to acid and RNAi mutants show a major SoMo defect similar to PDEB1 knockout phenotype (Shaw et al, 2021), whereas ablation and dominant-negative mutants of AC6, and dual ablation of AC1 and AC2, cause a hyper-social phenotype (Lopez et al, 2015). Cyclic nucleotides have already been proposed to regulate microbial social behaviour and this evidence suggests that this is also true in African trypanosomes.…”
Section: The Trypanosome Flagellum Is a Sensory Organellementioning
confidence: 99%
“…A surge of cyclic nucleotide-mediated response has been detected under temperature and pH stress, hypoxia, and depletion of nutrients like purines (Sen Santara et al, 2013;Saha et al, 2020;Kelly et al, 2021). In recent years, flagellar cAMP has surfaced as a major well-defined response in trypanosomatids with identified effectors like cAMP response proteins (CARPs) (Shaw et al, 2022). Though canonical Gprotein coupled receptors (GPCR) are apparently absent in trypanosomatids, putative orthologues with reduced domains have been annotated.…”
mentioning
confidence: 99%